Analysis of scientific literacy and reading skills in the topic of matter among primary school students - Ni Gusti Ayu Putu Eka Sri Wahyuni; Arum Maulidiyah; Afadil; Nurjannah; Karen Elinich (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2025)
This study aims to analyse the relationship between reading skills and science literacy in single substance and mixed substance materials in Year 5 primary school. This study uses a quantitative approach with descriptive and correlation analysis. The research sample consisted of 18 students at SD Negeri 2 Petobo. The instruments used were a reading skills test covering reading aloud, reading comprehension, reading speed, and text content analysis, as well as a science literacy test consisting of multiple-choice questions. The results of the Pearson correlation analysis showed a value of 0.6643, indicating a fairly strong positive relationship between reading skills and science literacy. The coefficient of determination (R²) of 0.4413 shows that approximately 44.13% of the variability in science literacy can be explained by reading skills. These findings emphasise the importance of reading skills in improving students' understanding of science material. This study is expected to contribute to the development of more effective science learning through the strengthening of students' reading skills. Analisis Literasi Sains dan Keterampilan Membaca Pada Materi Zat di kelas 5 Sekolah Dasar Penelitian ini bertujuan untuk menganalisis hubungan antara keterampilan membaca dan literasi sains pada materi zat tunggal dan zat campuran di kelas 5 SD. Penelitian ini menggunakan pendekatan kuantitatif dengan analisis deskriptif dan korelasi. Sampel penelitian terdiri dari 18 siswa di SD Negeri 2 Petobo. Instrumen yang digunakan adalah tes keterampilan membaca yang mencakup membaca nyaring, pemahaman bacaan, kecepatan membaca, dan analisis isi teks, serta tes literasi sains yang terdiri dari soal pilihan ganda. Hasil analisis korelasi Pearson menunjukkan nilai 0,6643, yang mengindikasikan adanya hubungan positif yang cukup kuat antara keterampilan membaca dan literasi sains. Koefisien determinasi (R²) sebesar 0,4413 menunjukkan bahwa sekitar 44,13% variabilitas literasi sains dapat dijelaskan oleh keterampilan membaca. Temuan ini menekankan pentingnya keterampilan membaca dalam meningkatkan pemahaman siswa terhadap materi sains. Penelitian ini diharapkan dapat memberikan kontribusi dalam pengembangan pembelajaran sains yang lebih efektif melalui penguatan keterampilan membaca siswa.